2020
DOI: 10.1080/15592294.2020.1782655
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal smoke exposure induces persistent Cyp2a5 methylation and increases nicotine metabolism in the liver of neonatal and adult male offspring

Abstract: Prenatal smoke exposure (PSE) is a risk factor for nicotine dependence. One susceptibility gene for nicotine dependence is Cytochrome P450 (CYP) 2A6, an enzyme responsible for the conversion of nicotine to cotinine and nicotine clearance in the liver. Higher activity of the CYP2A6 enzyme is associated with nicotine dependence, but no research has addressed the PSE effects on the CYP2A6 gene or its mouse homologue Cyp2a5 . We hypothesized that PSE affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…It is well known that smoke exposure effects on DNA methylation and gene expression are sex-dependent, as described by our research group [ 18 , 33 , 34 ] and others [ 28 , 29 , 30 , 35 , 36 ]. Similarly, we found that the distinct effects of PreSE and/ or PostSE on Cyp2a5 methylation, mRNA levels and the nicotine conversion rate were different in male and female offspring.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…It is well known that smoke exposure effects on DNA methylation and gene expression are sex-dependent, as described by our research group [ 18 , 33 , 34 ] and others [ 28 , 29 , 30 , 35 , 36 ]. Similarly, we found that the distinct effects of PreSE and/ or PostSE on Cyp2a5 methylation, mRNA levels and the nicotine conversion rate were different in male and female offspring.…”
Section: Discussionmentioning
confidence: 89%
“…Gene expression analysis in whole liver mRNA isolates was done via qPCR using qPCR MasterMix Plus (Eurogentec, Seraing, Belgium) with commercially available primers for Cyp2a4/5 (Mm00487248_m1, TaqMan ® Gene Expression Assay, Applied Biosystems, Foster City, CA, USA), Dnmt1 , Dnmt3a and Dnmt3b (Invitrogen, The Netherlands), and normalized to the housekeeping gene Gapdh (Mm99999915_m1, TaqMan ® Gene Expression Assay, Applied Biosystems, Foster City, CA, USA). Detection of amplification reactions was performed using the LightCycler ® 480 System (Roche Diagnostics GmbH, Mannheim, Germany), as previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations